TGF-β3 mediated chondrogenic differentiation of synovial mesenchymal stem cells in gene transferred co-culture systems - Rohan Rajeev Varshney (2011)
Articular degenerative diseases like osteoarthritis significantly affect the life quality of worldwide populations including Singaporean communities. Traditional approaches, typically transplantation of autologous tissue grafts, exhibit many limitations in clinic because of implants resorption and poor shaping with articular defects, as well as lack of sufficient materials donors. In the recent decade, novel strategies with tissue engineering and gene therapy have been developed from laboratory-based investigation to clinical applications. With the development of gene delivery to chondrocytic/progenitor therapeutic cells such as mesenchymal stem cells, treating disorders of articular cartilage by tissue engineering has borne much promise.